Antibacterial ultrathin inorganic artificial stone as well as preparation method and application thereof

By combining modified calcium carbonate powder and silver ion-treated fibers, the aging problem of antibacterial artificial stone in ultraviolet and high-temperature environments is solved, the antibacterial and mechanical properties of the material are improved, and the long-term stability of the antibacterial effect and the overall strength of the material are ensured.

CN120647251APending Publication Date: 2025-09-16CHINA RESOURCES CEMENT TECH R & D (GUANGXI) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510815933.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-18
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Existing antibacterial artificial stones are prone to aging under ultraviolet and high temperature environments, the molecular structure of the modified resin changes, and the antibacterial layer is easily worn or falls off, affecting the strength, stability and sanitary safety of the material. In addition, organic nanosilver has poor compatibility with the artificial stone matrix and is prone to forming microcracks.

Method used

Modified calcium carbonate powder and silver ion-treated fibers are used as antibacterial materials. By combining calcium carbonate powder modified with quaternary ammonium surfactants with silver ion-treated fibers, the antibacterial properties, mechanical properties and weather resistance of the material are improved, and the internal structure and antibacterial effect of the material are improved.

Benefits of technology

It improves the weather resistance and mechanical properties of antibacterial artificial stone, ensures the long-term stability of the antibacterial effect, reduces microcracks and interface defects, enhances the overall strength and stability of the material, and is suitable for applications requiring high strength and high stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120647251A_ABST
    Figure CN120647251A_ABST
Patent Text Reader

Abstract

The invention provides an antibacterial ultrathin inorganic artificial stone and a preparation method and application thereof, and relates to the technical field of artificial stone, the antibacterial ultrathin inorganic artificial stone comprises the following components: white cement, calcium powder, metakaolin, modified calcium carbonate powder, emulsion, modified fiber, a water reducing agent and water; the preparation method comprises the following steps: modifying calcium carbonate powder by adopting a quaternary ammonium salt surfactant to obtain modified calcium carbonate powder, and modifying fibers by adopting silver ions to obtain modified fibers. The weather resistance and the mechanical property of the material are improved while the material is endowed with the antibacterial property, so that the material can meet the strength and toughness requirements of the 10 mm ultrathin inorganic artificial stone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of artificial stones, and in particular to an antibacterial ultra-thin inorganic artificial stone and a preparation method and application thereof. Background Art

[0002] Artificial stone, a widely used building material, has seen increasing demand for its antibacterial properties in recent years. Currently, a variety of artificial stone products and preparation technologies with antibacterial properties exist.

[0003] CN202010115414.4 discloses an antibacterial artificial stone, a preparation method thereof, and a building material. The antibacterial artificial stone includes component A and component B. Component A includes the following raw materials: unsaturated polyester resin, aluminum hydroxide, methyl methacrylate, silane coupling agent, inorganic silver antibacterial agent, color paste, accelerator, and curing agent; and component B is color plate particles. The antibacterial artificial stone prepared by the embodiment of the present invention has an excellent antibacterial effect. The antibacterial artificial stone prepared by using an inorganic silver antibacterial agent has good antibacterial effect and stability and is non-toxic. The embodiment of the present invention also provides a preparation method for the antibacterial artificial stone. The use of an inorganic silver antibacterial agent and reasonable process conditions can ensure that the antibacterial agent is completely and evenly dispersed, thereby ensuring that there is no antibacterial blind spot at the microscopic level, solving the problem that existing artificial stones cannot maintain a good antibacterial effect while being non-toxic to the human body.

[0004] CN201910837209.6 discloses a long-lasting antibacterial artificial stone and its preparation process. The organic nanosilver prepared in the preparation process has better dispersibility and can be fully and evenly mixed with the raw materials of the artificial stone, so that the overall antibacterial effect of the green body of the long-lasting antibacterial artificial stone is better; and a surface antibacterial layer and an isolation layer to protect the surface antibacterial layer are added to the outside of the green body through a specific preparation process; so that the long-lasting antibacterial artificial stone has a more comprehensive antibacterial effect as a whole after production, which can fully meet the long-lasting antibacterial effect requirements of the long-lasting antibacterial artificial stone after it is cut and assembled in actual applications, and there will be no phenomenon that mold is easily bred at the assembly position of the artificial stone, so that the long-lasting antibacterial artificial stone has a more long-lasting and comprehensive antibacterial effect than the existing artificial stone.

[0005] CN201910813549.5 discloses a method for preparing an antibacterial artificial stone and an operating room wall panel using the stone. The preparation method comprises the following steps: (1) weighing each component in proportion, first adding epoxy resin, solvent, and antibacterial coupling agent into a reactor, stirring evenly to obtain a mixture; (2) adding aluminum hydroxide to the mixture obtained in step (1), stirring for 20-30 minutes, and then adding the remaining components, mixing evenly to obtain an artificial stone mixture; (3) pouring the mixture obtained in step (2) into a mold, pressing, and then heating and curing to obtain the antibacterial artificial stone; the components in step (1) are calculated by weight as follows: 30-50 parts of epoxy resin, 50-100 parts of quartz powder, 5-15 parts of aluminum hydroxide, 2-8 parts of antibacterial coupling agent, 0.5-5 parts of curing agent, 0.05-1 part of accelerator, and 3-10 parts of solvent. The antibacterial coupling agent is added to the artificial stone of the present invention, and the antibacterial component can be evenly dispersed in the artificial stone with the aid of the coupling agent, thereby achieving a good antibacterial effect.

[0006] Existing technologies primarily impart antibacterial properties by directly adding antimicrobial agents or modified resins. However, modified resins are susceptible to photodegradation and thermal degradation under ultraviolet light and high temperature conditions, causing changes in their molecular structure and, in turn, aging phenomena such as fading or yellowing, loss of luster and aesthetic appeal. These changes severely impact the product's appearance and quality, and reduce the mechanical properties of the resin, significantly impacting its strength and toughness. Over long-term use, especially under conditions of frequent friction and impact, the surface antimicrobial layer can easily wear out or fall off, exposing the antimicrobial ingredients to the outside world and losing their long-lasting antimicrobial effect. This increases the risk of bacterial growth and affects the hygienic safety of the antimicrobial artificial stone. Organic nanosilver has poor compatibility with the artificial stone matrix and can easily form microcracks or interface defects within the material. These defects act as stress concentration points, easily inducing crack propagation under external forces, thereby affecting the overall strength and stability of the material, reducing the structural integrity and durability of the antimicrobial artificial stone, and thus limiting its use in applications requiring high strength and stability.

[0007] In view of this, the present invention is proposed. Summary of the Invention

[0008] One of the objectives of the present invention is to provide an antibacterial ultra-thin inorganic artificial stone that addresses at least one of the technical problems existing in the prior art. By employing modified calcium carbonate powder and silver ion-treated fibers as antibacterial materials, the present invention not only imparts antibacterial properties to the material but also enhances its weather resistance and mechanical properties, enabling it to meet the strength and toughness requirements of 10mm ultra-thin inorganic artificial stone.

[0009] A second object of the present invention is to provide a method for preparing antibacterial ultra-thin inorganic artificial stone.

[0010] A third object of the present invention is to provide an antibacterial ultra-thin inorganic artificial stone or an application of a preparation method of an antibacterial ultra-thin inorganic artificial stone in the preparation of artificial stone.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are adopted:

[0012] In a first aspect, the present invention provides an antibacterial ultra-thin inorganic artificial stone comprising the following components: white cement, calcium powder, metakaolin, modified calcium carbonate powder, emulsion, modified fiber, water reducing agent and water;

[0013] The modified calcium carbonate powder is obtained by modifying the calcium carbonate powder with a quaternary ammonium salt surfactant, and the modified fiber is obtained by modifying the fiber with silver ions.

[0014] Furthermore, the modified calcium carbonate powder includes at least one of 40-mesh modified calcium carbonate powder, 60-mesh modified calcium carbonate powder and 90-mesh modified calcium carbonate powder;

[0015] And / or, the antibacterial ultra-thin inorganic artificial stone comprises the following components in parts by weight:

[0016] 20-28 parts of white cement, 3-7 parts of calcium powder, 1-4 parts of metakaolin, 10-15 parts of 40-mesh modified calcium carbonate powder, 15-25 parts of 60-mesh modified calcium carbonate powder, 25-35 parts of 90-mesh modified calcium carbonate powder, 2-4 parts of emulsion, 0.3-1 part of modified fiber, 1-2.5 parts of water reducer and 2-4 parts of water.

[0017] Further, the calcium carbonate powder is modified by a quaternary ammonium salt solution to obtain the modified calcium carbonate powder;

[0018] And / or, the mass ratio of the quaternary ammonium salt solution to the calcium carbonate powder is 0.1 to 0.2;

[0019] And / or, the concentration of the quaternary ammonium salt surfactant in the quaternary ammonium salt solution is 1%-5%;

[0020] And / or, the quaternary ammonium salt surfactant includes at least one of cetyltrimethylammonium chloride and cetyltrimethylammonium bromide.

[0021] Furthermore, the raw material of the modified fiber includes at least one of 6mm nylon fiber and 6mm polyester fiber;

[0022] and / or, modifying a modified fiber raw material by using a silver salt solution to obtain the modified fiber;

[0023] and / or, the mass ratio of the fiber to the silver salt solution is 0.1 to 0.2;

[0024] and / or, adding ammonia water at a ratio of 2 mL of concentrated ammonia water per gram of AgCl to the silver salt solution, slowly adding and stirring until dissolved, and finally adding deionized water to make up to volume;

[0025] and / or, the AgCl concentration in the silver salt solution is 1% to 5%;

[0026] And / or, during the treatment of the modified fiber, a glucose solution is further added, the mass ratio of the glucose solution to the silver salt solution is 0.5-1, and the concentration of the glucose solution is 10%-20%.

[0027] Furthermore, the white cement comprises at least one of Albow Cement PW-1 52.5 and Yingqi White Cement PW-152.5;

[0028] And / or, the metakaolin has a SiO2 content of ≥50% and an Al2O3 content of ≥35%;

[0029] And / or, the emulsion includes at least one of butadiene vinyl styrene copolymer emulsion, butadiene styrene emulsion, styrene acrylic emulsion, pure acrylic emulsion and acrylic acid emulsion.

[0030] In a second aspect, the present invention provides a method for preparing an antibacterial ultra-thin inorganic artificial stone, comprising the following steps:

[0031] The antibacterial ultra-thin inorganic artificial stone is obtained by mixing white cement, calcium powder, metakaolin, modified calcium carbonate powder, emulsion, modified fiber, water reducer and water in a prescribed amount, and then performing molding and curing treatment in sequence.

[0032] Furthermore, the preparation process of the modified calcium carbonate powder includes: mixing calcium carbonate powder with a quaternary ammonium salt solution, stirring at a speed of 600-1000 rpm for 20-30 minutes during the mixing process, then drying at a temperature of 25-50°C for 8-24 hours, and then drying at a temperature of 60-80°C for 3-12 hours to obtain the modified calcium carbonate powder.

[0033] Furthermore, the preparation process of the modified fiber includes: mixing the fiber with a silver salt solution, soaking the fiber at 25-60°C for 1-6 hours during the mixing process, then adding a glucose solution, reacting the fiber at 50-80°C for 3-12 hours, and heat-treating the fiber at 100-150°C for 0.25-1 hour after the reaction to obtain the modified fiber;

[0034] Furthermore, the mixing includes:

[0035] White cement, calcium powder, metakaolin and modified calcium carbonate powder are stirred at a speed of 200 to 500 rpm for 5 to 12 minutes, and then a water reducer, water and emulsion are added and stirred at a speed of 600 to 1000 rpm for a second time for 10 to 15 minutes, and then modified fiber is added and stirred at a speed of 1000 to 1300 rpm for a third time for 10 to 15 minutes to obtain a mixture, and the mixture is pressed and cured in sequence;

[0036] And / or, the curing time is 48 to 96 hours.

[0037] In a third aspect, the present invention provides an antibacterial ultra-thin inorganic artificial stone or an application of a method for preparing an antibacterial ultra-thin inorganic artificial stone in preparing artificial stone.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The antibacterial ultra-thin inorganic artificial stone provided by the present invention uses white cement as the main bonding material and calcium powder as the filler to improve the hardness, wear resistance and surface finish of the artificial stone. Metakaolin is used as a reinforcing agent to improve the heat resistance and corrosion resistance of the artificial stone. At the same time, the internal microstructure of the artificial stone can be improved to make it denser and more uniform. The emulsion is used as a toughening agent, which works synergistically with the white cement to further enhance the bonding effect. The components also include a water reducer to reduce water consumption without reducing the strength of the mixture, making the mixture easier to construct and shape.

[0040] The artificial stone component also includes modified calcium carbonate powder and modified fibers. During the processing of calcium carbonate powder, quaternary ammonium surfactants play an important role through their unique antibacterial mechanism and improved adhesion to the cement matrix. In terms of antibacterial properties, quaternary ammonium surfactants can destroy bacterial cell membranes, inhibit cell wall synthesis, and interfere with bacterial metabolic processes, thereby enhancing the inhibitory effect on drug-resistant bacteria. The large specific surface area of ​​calcium carbonate powder further enhances the antibacterial effect. Quaternary ammonium surfactants significantly improve the adhesion of calcium carbonate and cement matrix by improving surface affinity, improving wettability, promoting the combination of cement hydration products, and improving dispersibility, thereby enhancing the mechanical properties, stability, and durability of the cement matrix. In addition, quaternary ammonium surfactants have strong hydrophilicity and surface adsorption, and can effectively fix the silver ions released on the fiber to the surface or internal structure of the material, ensuring the long-term release of silver ions, further enhancing the antibacterial effect. The silver ion-treated fiber not only serves as a carrier for the antibacterial agent, but also significantly improves the mechanical properties of the artificial stone after addition.

[0041] This invention innovatively enhances the material's antimicrobial, mechanical, and weatherability properties by combining calcium carbonate powder modified with a quaternary ammonium surfactant with silver ion-treated fibers. The synergistic effect of the quaternary ammonium surfactant and silver ions effectively enhances the antimicrobial effect while also improving the material's weatherability and mechanical properties. This results in a 10mm ultra-thin inorganic artificial stone with excellent strength and toughness while maintaining superior antimicrobial properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0043] Figure 1 A front view provided for Example 10;

[0044] Figure 2 A side view provided for Example 10;

[0045] Figure 3 A side view provided for Comparative Example 6;

[0046] Figure 4 This is a graph analyzing the antibacterial test data immediately after inoculation;

[0047] Figure 5 This is the antibacterial test data analysis chart 24 hours after inoculation;

[0048] Figure 6 This is the antibacterial test data analysis chart 168 hours after inoculation;

[0049] Figure 7 This is the antibacterial test data analysis chart 720 hours after inoculation;

[0050] Figure 8 1 is a graph of flexural test data, in which Samples 1 to 14 correspond to Comparative Example 2, Comparative Example 4, Comparative Example 6, Comparative Example 8, Comparative Example 10, Example 8, Example 9, Example 10, Example 11, Example 12, Example 13, Example 14, Example 15, and Example 16 respectively;

[0051] Figure 9 This is the experimental site photo of the flexural test;

[0052] Figure 10 This is a front view of the falling ball impact test equipment;

[0053] Figure 11 Side view of the falling ball impact test equipment. DETAILED DESCRIPTION

[0054] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear; however, in the event of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, the use of "or" means "and / or" unless otherwise stated. In addition, the use of the term "including" and other forms is non-limiting.

[0055] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0056] The first aspect of the present invention provides an antibacterial ultra-thin inorganic artificial stone, comprising the following components: white cement, calcium powder, metakaolin, modified calcium carbonate powder, emulsion, modified fiber, water reducing agent and water;

[0057] The modified calcium carbonate powder is obtained by modifying the calcium carbonate powder with a quaternary ammonium salt surfactant, and the modified fiber is obtained by modifying the fiber with silver ions.

[0058] Among them, the calcium powder is preferably 200 mesh calcium powder, and the water reducer is preferably polycarboxylic acid early strength type _CSP-12 water reducer.

[0059] In some preferred embodiments, the modified calcium carbonate powder includes at least one of 40-mesh modified calcium carbonate powder, 60-mesh modified calcium carbonate powder, and 90-mesh modified calcium carbonate powder.

[0060] And / or, the antibacterial ultra-thin inorganic artificial stone comprises the following components in parts by weight:

[0061] 20-28 parts of white cement, 3-7 parts of calcium powder, 1-4 parts of metakaolin, 10-15 parts of 40-mesh modified calcium carbonate powder, 15-25 parts of 60-mesh modified calcium carbonate powder, 25-35 parts of 90-mesh modified calcium carbonate powder, 2-4 parts of emulsion, 0.3-1 part of modified fiber, 1-2.5 parts of water reducer and 2-4 parts of water.

[0062] In the antibacterial ultra-thin inorganic artificial stone, the addition amount of white cement is 20 to 28 parts, for example, it can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, etc.

[0063] In the antibacterial ultra-thin inorganic artificial stone, the amount of calcium powder added is 3 to 7 parts, for example, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, etc.;

[0064] In the antibacterial ultra-thin inorganic artificial stone, the addition amount of metakaolin is 1 to 4 parts, for example, 1 part, 2 parts, 3 parts, 4 parts, etc.;

[0065] In the antibacterial ultra-thin inorganic artificial stone, the addition amount of 40-mesh modified calcium carbonate powder is 10 to 15 parts, for example, it can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc.;

[0066] In the antibacterial ultra-thin inorganic artificial stone, the addition amount of 60-mesh modified calcium carbonate powder is 15 to 25 parts, for example, 15 parts, 20 parts, 25 parts, etc.;

[0067] In the antibacterial ultra-thin inorganic artificial stone, the addition amount of 90-mesh modified calcium carbonate powder is 25 to 35 parts, for example, 25 parts, 30 parts, 35 parts, etc.;

[0068] In the antibacterial ultra-thin inorganic artificial stone, the amount of the emulsion added is 2 to 4 parts, for example, 2 parts, 3 parts, 4 parts, etc.;

[0069] In the antibacterial ultra-thin inorganic artificial stone, the added amount of modified fiber is 0.3 to 1 part, for example, it can be 0.3 part, 0.5 part, 1 part, etc.

[0070] In the antibacterial ultra-thin inorganic artificial stone, the amount of the water reducer added is 1 to 2.5 parts, for example, 1 part, 1.5 parts, 2 parts, 2.5 parts, etc.;

[0071] In the antibacterial ultra-thin inorganic artificial stone, the amount of water added is 2 to 4 parts, for example, 2 parts, 3 parts, 4 parts, etc.

[0072] In some preferred embodiments, the modified calcium carbonate powder is obtained by modifying the calcium carbonate powder with a quaternary ammonium salt solution.

[0073] Among the present invention, in the processing of calcium carbonate powder, quaternary ammonium salt surfactant plays an important role by its unique antibacterial mechanism and improving the bonding force with cement matrix. In terms of antibacterial, quaternary ammonium salt surfactant can destroy bacterial cell membrane, inhibit cell wall synthesis, and interfere with the metabolic process of bacteria, thereby strengthening the inhibitory effect of drug-resistant bacteria. The larger specific surface area of ​​calcium carbonate powder further enhances antibacterial effect. In cement matrix applications, quaternary ammonium salt surfactant significantly improves the bonding force of both by improving the surface affinity of calcium carbonate and cement matrix, improving wettability, promoting the combination of cement hydration products and improving dispersibility, thereby strengthening the mechanical property, stability and the durability of cement matrix. In addition, quaternary ammonium salt surfactant has strong hydrophilicity and surface adsorption, can effectively be fixed on the surface or internal structure of the silver ion discharged on the fiber, guarantees the long-term release of silver ion, further enhances antibacterial effect. The fiber treated with silver ion not only as the carrier of antibacterial agent, but also significantly improves the mechanical property of artificial stone after adding.

[0074] And / or, the mass ratio of the quaternary ammonium salt solution to the calcium carbonate powder is 0.1 to 0.2, for example, 0.1, 0.15, 0.2, etc.;

[0075] And / or, the concentration of the quaternary ammonium salt surfactant in the quaternary ammonium salt solution is 1%-5%, for example, 1%, 2%, 3%, 4%, 5%, etc.;

[0076] And / or, the quaternary ammonium salt surfactant includes at least one of cetyltrimethylammonium chloride and cetyltrimethylammonium bromide.

[0077] In some preferred embodiments, the modified fiber raw material includes at least one of 6 mm nylon fiber and 6 mm polyester fiber;

[0078] and / or, modifying a modified fiber raw material by using a silver salt solution to obtain the modified fiber;

[0079] and / or, the mass ratio of the fiber to the silver salt solution is 0.1 to 0.2, for example, 0.1, 0.15, 0.2, etc.;

[0080] And / or, the concentration of AgCl in the silver salt solution is 1% to 5%, for example, 1%, 2%, 3%, 4%, 5%, etc.

[0081] And / or, the silver salt solution is added with ammonia water at a ratio of 2 mL of concentrated ammonia water per gram of AgCl, slowly added and stirred until dissolved, and finally deionized water is added to make up the volume.

[0082] And / or, during the treatment of the modified fiber, a glucose solution is further added, the mass ratio of the glucose solution to the silver salt solution is 0.5-1, for example, it can be 0.5, 0.8, 0.5, etc.; the concentration of the glucose solution is 10%-20%, for example, it can be 10%, 15%, 20%, etc.

[0083] In some preferred embodiments, the white cement includes at least one of Albaugh Cement PW-1 52.5 and Yingqi White Cement PW-1 52.5;

[0084] And / or, the metakaolin has a SiO2 content of ≥50% and an Al2O3 content of ≥35%;

[0085] And / or, the emulsion includes at least one of butadiene vinyl styrene copolymer emulsion, butadiene styrene emulsion, styrene acrylic emulsion, pure acrylic emulsion and acrylic acid emulsion.

[0086] A second aspect of the present invention provides a method for preparing an antibacterial ultra-thin inorganic artificial stone, comprising the following steps:

[0087] The antibacterial ultra-thin inorganic artificial stone is obtained by mixing white cement, calcium powder, metakaolin, modified calcium carbonate powder, emulsion, modified fiber, water reducer and water in a prescribed amount, and then performing molding and curing treatment in sequence.

[0088] In some preferred embodiments, the preparation process of the modified calcium carbonate powder includes: mixing calcium carbonate powder with a quaternary ammonium salt solution, stirring at a speed of 600 to 1000 rpm for 20 to 30 minutes during the mixing process, then drying at a temperature of 25 to 50° C. for 8 to 24 hours, and then drying at a temperature of 60 to 80° C. for 3 to 12 hours to obtain the modified calcium carbonate powder.

[0089] Here, “600-1000 rpm” can be, for example, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, etc.;

[0090] Here, “20 to 30 minutes” can be, for example, 20 minutes, 25 minutes, 30 minutes, etc.

[0091] Here, “25-50°C” can be, for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, etc.;

[0092] Among them, "8~24h" can be, for example, 8h, 12h, 16h, 24h, etc.;

[0093] Here, "60-80°C" can be, for example, 60°C, 70°C, 80°C, etc.;

[0094] Here, “3 to 12 hours” can be, for example, 3 hours, 5 hours, 10 hours, 12 hours, etc.

[0095] In some preferred embodiments, the preparation process of the modified fiber includes: mixing the fiber with a silver salt solution, soaking the fiber at 25-60°C for 1-6 hours during the mixing process, then adding a glucose solution, reacting at 50-80°C for 3-12 hours, and after the reaction is completed, heat treating the fiber at 100-150°C for 0.25 hours to 1 hour to obtain the modified fiber.

[0096] In the present invention, the glucose solution mainly acts as a reducing agent to promote the reduction reaction of the silver salt and help the silver ions form nanosilver particles on the fiber surface. The modified fiber can only be prepared after the glucose solution reduction treatment.

[0097] Here, “25-60°C” can be, for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, etc.;

[0098] Here, “1 to 6 hours” can be, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, etc.;

[0099] Here, "50-80°C" can be, for example, 50°C, 60°C, 70°C, 80°C, etc.;

[0100] Here, "3-12h" can be, for example, 3h, 5h, 10h, 12h, etc.

[0101] Here, "100-150°C" can be, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc.;

[0102] Here, “0.25h~1h” can be, for example, 0.25h, 0.5h, 1h, etc.

[0103] In some preferred embodiments, the mixing comprises:

[0104] White cement, calcium powder, metakaolin and modified calcium carbonate powder are stirred at a speed of 200 to 500 rpm for 5 to 12 minutes, and then a water reducer, water and emulsion are added and stirred at a speed of 600 to 1000 rpm for a second time for 10 to 15 minutes, and then modified fiber is added and stirred at a speed of 1000 to 1300 rpm for a third time for 10 to 15 minutes to obtain a mixture, and the mixture is pressed and cured in sequence;

[0105] Here, “200-500 rpm” can be, for example, 200 rpm, 300 rpm, 400 rpm, 500 rpm, etc.;

[0106] Here, “5 to 12 minutes” can be, for example, 5 minutes, 10 minutes, 12 minutes, etc.;

[0107] Here, “600-1000 rpm” can be, for example, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, etc.;

[0108] Here, “10-15 minutes” can be, for example, 10 minutes, 12 minutes, 15 minutes, etc.;

[0109] Here, “1000 rpm to 1300 rpm” may be, for example, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, etc.

[0110] And / or, the curing time is 48 to 96 hours, for example, 48 hours, 72 hours, 96 hours, etc.

[0111] In the optional solution of the present invention, preferably, the method for preparing the antibacterial ultra-thin inorganic artificial stone specifically comprises the following steps:

[0112] After weighing the materials in the formula, first pour white cement, 200 mesh calcium powder, metakaolin, and modified calcium carbonate powder into the mixer in sequence, and stir at a speed of 200-500 rpm for 5-12 minutes; after sufficient stirring, add water reducer, water, and polymer emulsion in sequence, and stir for a second time at a speed of 600-1000 rpm for 10-15 minutes; after sufficient secondary stirring, add modified fiber, and stir for a third time at a speed of 1000-1300 rpm for 10-15 minutes, then pour the obtained mixture into a mold and place it in a press for pressing. After the pressing is completed, the obtained rough material is cured at room temperature for 48-96 hours. After the curing is completed, the obtained square material is cut to 11 mm and polished to 10 mm to obtain the antibacterial ultra-thin inorganic artificial stone.

[0113] The modified calcium carbonate powder is prepared as follows:

[0114] First, the calcium carbonate powder is cleaned and dried, and then a quaternary ammonium salt solution is prepared (a quaternary ammonium salt surfactant is dissolved in ethanol to obtain a quaternary ammonium salt solution with a concentration of 1% to 5%), and the dried calcium carbonate powder is added to the solution, and the mass ratio of the quaternary ammonium salt solution to the calcium carbonate powder is 0.1 to 0.2. After stirring in a blender at a speed of 600 to 1000 rpm for 20 to 30 minutes, the treated powder is placed in an oven at 25 to 50° C. for 8 to 24 hours, and then the temperature is increased to 60 to 80° C. and placed for 3 to 12 hours to remove residual solvent and moisture, thereby obtaining a modified calcium carbonate powder.

[0115] The fiber modification steps used are:

[0116] First, the fiber surface is cleaned and dried. Then, the fiber is immersed in a silver salt solution (a 1% to 5% AgCl solution, prepared by adding ammonia water at a ratio of 2 mL of concentrated ammonia water per gram of AgCl, slowly adding and stirring until dissolved, and finally adding deionized water to make up the volume) according to a mass ratio of fiber to silver salt solution of 0.1 to 0.2, and soaked at 25 to 60° C. for 1 to 6 hours. After soaking, a 10% to 20% glucose solution is added according to a mass ratio of glucose solution to silver salt solution of 0.5 to 1, and reacted at 50 to 80° C. for 3 to 12 hours. After the reaction is completed, the fiber is filtered out and placed in an oven for heat treatment at 100 to 150° C. for 0.25 to 1 hour. After the treatment, the fiber is washed with deionized water several times and naturally dried to ensure that the fiber is completely dry.

[0117] The antibacterial ultra-thin inorganic artificial stone and its preparation method provided by the present invention can solve the defects of existing antibacterial artificial stone technology, such as aging resistance, mechanical property limitations, poor durability of the antibacterial layer, and material compatibility problems. By adopting modified calcium carbonate powder and silver ion-treated fibers as antibacterial materials, the material is given antibacterial properties while improving the weather resistance and mechanical properties of the material, so that it can meet the strength and toughness requirements of 10mm ultra-thin inorganic artificial stone. In addition, the present invention optimizes the distribution and release mechanism of the antibacterial components, realizes the long-term stable release of the antibacterial components, and avoids the decline in antibacterial performance caused by wear or shedding of the antibacterial layer. At the same time, the modified calcium carbonate powder and silver ion-treated fibers have good compatibility with the inorganic artificial stone matrix, reduce the microcracks and interface defects inside the material, improve the overall strength and stability of the material, ensure the high quality and reliability of the antibacterial ultra-thin inorganic artificial stone, and make it more suitable for large-scale production and promotion and application.

[0118] A third aspect of the present invention provides an antibacterial ultra-thin inorganic artificial stone or an application of a method for preparing an antibacterial ultra-thin inorganic artificial stone in preparing artificial stone.

[0119] The present invention provides an inorganic artificial stone, which is an ultra-thin inorganic artificial stone with antibacterial properties. The preparation method of the antibacterial ultra-thin inorganic artificial stone mainly uses a specific process to give it an antibacterial function and prepare it into an ultra-thin plate or sheet. While maintaining its excellent mechanical properties, durability and aesthetics, it imparts an antibacterial effect. This type of material is widely used in the fields of construction, decoration, sanitary facilities, etc., and is particularly suitable for environments that require antibacterial, mildew-proof and anti-fouling properties. This method can introduce antibacterial components into the ultra-thin artificial stone material by optimizing the production process, thereby improving its surface antibacterial properties and is widely used in kitchens, bathrooms, hospitals, businesses and other places.

[0120] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.

[0121] It should be noted that in the metakaolin in the following examples and comparative examples, the SiO2 content is ≥50% and the Al2O3 content is ≥35%.

[0122] The preparation method of the silver salt solution involved in the following examples and comparative examples is as follows: add ammonia water at a ratio of 2 mL of concentrated ammonia water per gram of AgCl to the silver salt solution, slowly add and stir until dissolved, and finally add deionized water to make the volume to the required volume to meet the concentration requirements of the silver salt solution in the following examples and comparative examples.

[0123] Example 1

[0124] This embodiment provides an antibacterial ultra-thin inorganic artificial stone, comprising the following components: 25 parts of Alborg white cement PW-152.5, 5 parts of 200-mesh calcium powder, 2 parts of metakaolin, 13 parts of modified calcium carbonate powder 40 mesh, 18 parts of modified calcium carbonate powder 60 mesh, 30.5 parts of modified calcium carbonate powder 90 mesh, 3 parts of styrene-butadiene emulsion, 0.3 parts of modified 6mm nylon fiber, 2 parts of water, and 1.5 parts of polycarboxylic acid early strength type_CSP-12 water reducer.

[0125] wherein calcium carbonate powder is modified by a quaternary ammonium salt solution to obtain the modified calcium carbonate powder; the mass ratio of the quaternary ammonium salt solution to the calcium carbonate powder is 0.1; the concentration of the quaternary ammonium salt surfactant (hexadecyltrimethylammonium chloride is selected) in the quaternary ammonium salt solution is 3%;

[0126] The modified fiber raw material is modified by a silver salt solution to obtain a modified fiber, wherein the mass ratio of the fiber to the silver salt solution is 0.1; the AgCl concentration in the silver salt solution is 3%; during the treatment of the modified fiber, a glucose solution is also added, the mass ratio of the glucose solution to the silver salt solution is 0.75, and the concentration of the glucose solution is 15%.

[0127] Example 2

[0128] This embodiment provides an antibacterial ultra-thin inorganic artificial stone, which differs from Example 1 in that: 0.5 parts of modified 6mm nylon fiber is added;

[0129] wherein calcium carbonate powder is modified by a quaternary ammonium salt solution to obtain the modified calcium carbonate powder; the mass ratio of the quaternary ammonium salt solution to the calcium carbonate powder is 0.2; the concentration of the quaternary ammonium salt surfactant (hexadecyltrimethylammonium chloride is selected) in the quaternary ammonium salt solution is 5%;

[0130] The modified fiber raw material is modified by a silver salt solution to obtain a modified fiber, wherein the mass ratio of the fiber to the silver salt solution is 0.2; the AgCl concentration in the silver salt solution is 5%; during the treatment of the modified fiber, a glucose solution is also added, wherein the mass ratio of the glucose solution to the silver salt solution is 1, and the concentration of the glucose solution is 20%;

[0131] The remaining components are the same as those in Example 1.

[0132] Example 3

[0133] This embodiment provides an antibacterial ultra-thin inorganic artificial stone, which differs from Example 2 in that modified 6mm polyester fiber is selected and added in an amount of 0.5 parts, and the other components are the same as those in Example 2.

[0134] Example 4

[0135] This embodiment provides an antibacterial ultra-thin inorganic artificial stone, comprising the following components:

[0136] 20 parts of Aalborg white cement PW-1 52.5, 7 parts of 200-mesh calcium powder, 1 part of metakaolin, 15 parts of 40-mesh, 15 parts of 60-mesh, 35 parts of 90-mesh calcium carbonate powder, 2 parts of styrene-butadiene emulsion, 1 part of modified 6mm nylon fiber, 2 parts of water, and 1.5 parts of polycarboxylic acid early-strength type CSP-12 water reducer;

[0137] The formula of modified calcium carbonate powder and modified fiber is consistent with that of Example 3.

[0138] Example 5

[0139] This embodiment provides an antibacterial ultra-thin inorganic artificial stone, comprising the following components:

[0140] 26 parts of Aalborg white cement PW-1 52.5, 3 parts of 200-mesh calcium powder, 4 parts of metakaolin, 10 parts of 40-mesh calcium carbonate powder, 23 parts of 60-mesh calcium carbonate powder, 25 parts of 90-mesh calcium carbonate powder, 4 parts of styrene-butadiene emulsion, 0.3 parts of modified 6mm nylon fiber, 4 parts of water, and 1 part of polycarboxylic acid early-strength type CSP-12 water reducer;

[0141] The formula of modified calcium carbonate powder and modified fiber is consistent with that of Example 3.

[0142] Example 6

[0143] This embodiment provides an antibacterial ultra-thin inorganic artificial stone, which has the same raw material components as Example 3, and the difference from Example 3 is:

[0144] The modified calcium carbonate powder is modified by using a quaternary ammonium salt solution to obtain the modified calcium carbonate powder; the mass ratio of the quaternary ammonium salt solution to the calcium carbonate powder is 0.05; the concentration of the quaternary ammonium salt surfactant (hexadecyltrimethylammonium chloride is selected) in the quaternary ammonium salt solution is 6%;

[0145] The modified fiber raw material is modified by a silver salt solution to obtain a modified fiber, wherein the mass ratio of the fiber to the silver salt solution is 0.3; the AgCl concentration in the silver salt solution is 1%; during the treatment of the modified fiber, a glucose solution is also added, wherein the mass ratio of the glucose solution to the silver salt solution is 0.4, and the concentration of the glucose solution is 25%;

[0146] The rest is consistent with Example 3.

[0147] Example 7

[0148] This embodiment provides an antibacterial ultra-thin inorganic artificial stone, which has the same raw material components as Example 3, and the difference from Example 3 is:

[0149] Modifying calcium carbonate powder by using a quaternary ammonium salt solution to obtain the modified calcium carbonate powder; the mass ratio of the quaternary ammonium salt solution to the calcium carbonate powder is 0.3; the concentration of the quaternary ammonium salt surfactant (hexadecyltrimethylammonium chloride is selected) in the quaternary ammonium salt solution is 1%;

[0150] The modified fiber raw material is modified by a silver salt solution to obtain a modified fiber, wherein the mass ratio of the fiber to the silver salt solution is 0.06; the AgCl concentration in the silver salt solution is 6%; during the treatment of the modified fiber, a glucose solution is also added, the mass ratio of the glucose solution to the silver salt solution is 1.1, and the concentration of the glucose solution is 10%;

[0151] The rest is consistent with Example 3.

[0152] Example 8

[0153] This embodiment provides a method for preparing an antibacterial ultra-thin inorganic artificial stone, using the raw material formula of Example 1, and specifically comprising the following steps:

[0154] After weighing the materials in the formula, white cement, 200 mesh calcium powder, metakaolin, and modified calcium carbonate powder are poured into the mixer in sequence and stirred at a speed of 300 rpm for 8 minutes; after sufficient stirring, water reducer, water, and polymer emulsion are added in sequence, and stirred for a second time at a speed of 800 rpm for 12 minutes; after sufficient secondary stirring, modified fiber is added, and stirred for three times at a speed of 1200 rpm for 12 minutes, and the resulting mixture is poured into a mold and placed in a press for pressing. After the pressing is completed, the obtained rough material is cured at room temperature for 72 hours. After the curing is completed, the obtained square material is cut to 11 mm and polished to 10 mm to obtain the antibacterial high-toughness ultra-thin inorganic artificial stone;

[0155] The modified calcium carbonate powder used is prepared as follows:

[0156] First, the calcium carbonate powder is cleaned and dried, and then a 3% cetyltrimethylammonium chloride solution (cetyltrimethylammonium chloride is dissolved in ethanol) is prepared, and the dried calcium carbonate powder is added to the solution, according to the mass ratio of the quaternary ammonium salt solution to the calcium carbonate powder of 0.1, after stirring at a speed of 800 rpm in a blender for 30 minutes, the treated powder is placed in an oven at 40°C for 24 hours, and then the temperature is increased to 80°C and placed for 6 hours to remove residual solvent and moisture, thereby obtaining a modified calcium carbonate powder;

[0157] The modified fiber steps used are: first, the nylon fiber surface is cleaned and dried, then, the fiber is immersed in a 3% AgCl solution at a mass ratio of 0.1 between the fiber and the silver salt solution, and immersed at 30°C for 6 hours. After soaking, 15% glucose solution is added at a mass ratio of 0.75 between the glucose solution and the silver salt solution, and the reaction is carried out at 60°C for 9 hours. After the reaction, the fiber is filtered out and placed in an oven for heat treatment at 120°C for 1 hour. After the treatment, the fiber is washed with deionized water several times and the fiber is naturally dried to ensure that the fiber is completely dry.

[0158] Examples 9-14

[0159] Examples 9-14 provide a method for preparing an antibacterial ultra-thin inorganic artificial stone, using the raw material formulas of Examples 2-7 respectively, and the preparation steps are consistent with Example 8.

[0160] Example 15

[0161] This embodiment provides a method for preparing an antibacterial ultra-thin inorganic artificial stone, using the raw material formula of Example 3, and specifically comprising the following steps:

[0162] After weighing the materials in the formula, first pour white cement, 200 mesh calcium powder, metakaolin, and modified calcium carbonate powder into the mixer in sequence, and stir at a speed of 200 rpm for 12 minutes; after stirring sufficiently, add water reducer, water, and polymer emulsion in sequence, and stir for a second time at a speed of 600 rpm for 15 minutes; after the second stirring is sufficient, add modified fiber, and stir for a third time at a speed of 1000 rpm for 15 minutes, then pour the obtained mixture into a mold and place it in a press for pressing. After the pressing is completed, the obtained rough material is cured at room temperature for 48 hours. After the curing is completed, the obtained square material is cut to 11 mm and polished to 10 mm to obtain the antibacterial and high-toughness ultra-thin inorganic artificial stone.

[0163] The modified calcium carbonate powder used therein is prepared by first cleaning and drying the calcium carbonate powder, then preparing a 5% cetyltrimethylammonium bromide solution (cetyltrimethylammonium bromide dissolved in ethanol), and adding the dried calcium carbonate powder to the solution, with a mass ratio of quaternary ammonium salt solution to calcium carbonate powder of 0.2. After stirring in a blender at a speed of 600 rpm for 30 minutes, the treated powder is placed in an oven at 25°C for 24 hours, and then the temperature is increased to 60°C and placed for 12 hours to remove residual solvent and moisture, thereby obtaining the modified calcium carbonate powder.

[0164] The fiber modification steps used are as follows: first, the surface of the polyester fiber is cleaned and dried; then, the fiber is immersed in a 5% AgCl solution at a mass ratio of 0.2 between the fiber and the silver salt solution, and immersed at 25°C for 6 hours; after the immersion, a 20% glucose solution is added at a mass ratio of 1 between the glucose solution and the silver salt solution, and the mixture is reacted at 50°C for 12 hours; after the reaction, the fiber is filtered out and placed in an oven for heat treatment at 100°C for 1 hour; after the treatment, the fiber is washed with deionized water several times and dried naturally to ensure that the fiber is completely dry.

[0165] Example 16

[0166] This embodiment provides a method for preparing an antibacterial ultra-thin inorganic artificial stone, using the raw material formula of Example 3, and specifically comprising the following steps:

[0167] After weighing the materials in the formula, first pour white cement, 200 mesh calcium powder, metakaolin, and modified calcium carbonate powder into the mixer in sequence, and stir at a speed of 500 rpm for 5 minutes; after stirring sufficiently, add water reducer, water, and polymer emulsion in sequence, and stir for a second time at a speed of 1000 rpm for 10 minutes; after the second stirring is sufficient, add modified fiber, and stir for a third time at a speed of 1300 rpm for 10 minutes, then pour the obtained mixture into a mold and place it in a press for pressing. After the pressing is completed, the obtained rough material is cured at room temperature for 96 hours. After the curing is completed, the obtained square material is cut to 11 mm and polished to 10 mm to obtain the antibacterial and high-toughness ultra-thin inorganic artificial stone.

[0168] The modified calcium carbonate powder used therein is prepared by first cleaning and drying the calcium carbonate powder, then preparing a 5% cetyltrimethylammonium bromide solution (cetyltrimethylammonium bromide dissolved in ethanol), and adding the dried calcium carbonate powder to the solution, with a mass ratio of quaternary ammonium salt solution to calcium carbonate powder of 0.2. After stirring in a blender at a speed of 1000 rpm for 20 minutes, the treated powder is placed in an oven at 55°C for 8 hours, and then the temperature is increased to 80°C and placed for 3 hours to remove residual solvent and moisture, thereby obtaining the modified calcium carbonate powder.

[0169] The fiber modification steps used are as follows: first, the surface of the polyester fiber is cleaned and dried; then, the fiber is immersed in a 5% AgCl solution at a mass ratio of 0.2 between the fiber and the silver salt solution, and immersed at 60°C for 1 hour; after the immersion, a 20% glucose solution is added at a mass ratio of 1 between the glucose solution and the silver salt solution, and the mixture is reacted at 80°C for 3 hours; after the reaction, the fiber is filtered out and placed in an oven for heat treatment at 150°C for 0.25 hours; after the treatment, the fiber is washed with deionized water several times and dried naturally to ensure that the fiber is completely dry.

[0170] Comparative Example 1

[0171] This comparative example uses an inorganic artificial stone, the formula of which differs from that of Example 1 in that no modified fiber is added and the calcium carbonate powder is not modified;

[0172] The specific formula of Comparative Example 1 is: 25 parts of Alborg white cement PW-1 52.5, 5 parts of 200 mesh calcium powder, 2 parts of metakaolin, 13 parts of 40 mesh calcium carbonate powder, 18 parts of 60 mesh calcium carbonate powder, 30.5 parts of 90 mesh calcium carbonate powder, 3 parts of styrene-butadiene emulsion, 2 parts of water, and 1.5 parts of polycarboxylic acid early strength type_CSP-12 water reducer.

[0173] Comparative Example 2

[0174] This comparative example uses a method for preparing inorganic artificial stone, using the formula of comparative example 1 for preparation, comprising the following steps:

[0175] After the above materials are weighed, white cement, 200 mesh calcium powder, metakaolin, and calcium carbonate powder are poured into the mixer in sequence and stirred at a speed of 300 rpm for 8 minutes; after sufficient stirring, water reducer, water, and polymer emulsion are added in sequence, and stirred for a second time at a speed of 800 rpm for 12 minutes. The obtained mixture is poured into a mold and placed in a press for pressing. After the pressing is completed, the obtained rough material is cured at room temperature for 72 hours. After the curing is completed, the obtained square material is cut to 11 mm and polished to 10 mm to obtain the inorganic artificial stone.

[0176] Comparative Example 3

[0177] This comparative example uses an inorganic artificial stone, the formula of which differs from that of Example 1 in that no modified fiber is added;

[0178] The specific formula of Comparative Example 3 is: 25 parts of Alborg white cement PW-1 52.5, 5 parts of 200 mesh calcium powder, 2 parts of metakaolin, 13 parts of modified calcium carbonate powder 40 mesh, 18 parts of 60 mesh, 30.5 parts of 90 mesh, 3 parts of styrene-butadiene emulsion, 2 parts of water, and 1.5 parts of polycarboxylic acid early strength type_CSP-12 water reducer.

[0179] Comparative Example 4

[0180] This comparative example uses a method for preparing inorganic artificial stone, using the formula of comparative example 3 for preparation, comprising the following steps:

[0181] After the above materials are weighed, white cement, 200 mesh calcium powder, metakaolin, and modified calcium carbonate powder are poured into the mixer in sequence and stirred at a speed of 300 rpm for 8 minutes; after sufficient stirring, water reducer, water, and polymer emulsion are added in sequence, and stirred for a second time at a speed of 800 rpm for 12 minutes. The obtained mixture is poured into a mold and placed in a press for pressing. After the pressing is completed, the obtained rough material is cured at room temperature for 72 hours. After the curing is completed, the obtained square material is cut to 11 mm and polished to 10 mm to obtain the inorganic artificial stone.

[0182] The preparation steps of the modified calcium carbonate powder used therein are consistent with the preparation steps of the modified calcium carbonate powder in Example 8.

[0183] Comparative Example 5

[0184] This comparative example uses an inorganic artificial stone, the formula of which differs from that of Example 1 in that neither the calcium carbonate powder nor the fiber is modified;

[0185] The specific formula of Comparative Example 5 is: 25 parts of Alborg white cement PW-1 52.5, 5 parts of 200 mesh calcium powder, 2 parts of metakaolin, 13 parts of 40 mesh calcium carbonate powder, 18 parts of 60 mesh calcium carbonate powder, 30.5 parts of 90 mesh calcium carbonate powder, 3 parts of styrene-butadiene emulsion, 0.3 parts of 6mm nylon fiber, 2 parts of water, and 1.5 parts of polycarboxylic acid early strength type_CSP-12 water reducer.

[0186] Comparative Example 6

[0187] This comparative example uses a method for preparing inorganic artificial stone, using the formula of comparative example 5 for preparation, comprising the following steps:

[0188] After the above materials are weighed, white cement, 200 mesh calcium powder, metakaolin, and calcium carbonate powder are poured into the mixer in sequence and stirred at a speed of 300 rpm for 8 minutes; after sufficient stirring, water reducer, water, and polymer emulsion are added in sequence and stirred for a second time at a speed of 800 rpm for 12 minutes; after the second stirring is sufficient, fiber is added and stirred for a third time at a speed of 1200 rpm for 12 minutes, and the obtained mixture is poured into a mold and placed in a press for pressing. After the pressing is completed, the obtained rough material is cured at room temperature for 72 hours. After the curing is completed, the obtained square material is cut to 11 mm and polished to 10 mm to obtain the inorganic artificial stone.

[0189] Comparative Example 7

[0190] This comparative example uses an inorganic artificial stone, the formula of which differs from that of Example 1 in that the fibers are not modified;

[0191] The specific formula of Comparative Example 7 is: 25 parts of Alborg white cement PW-1 52.5, 5 parts of 200 mesh calcium powder, 2 parts of metakaolin, 13 parts of modified calcium carbonate powder 40 mesh, 18 parts of 60 mesh, 30.5 parts of 90 mesh, 3 parts of styrene-butadiene emulsion, 0.3 parts of 6mm nylon fiber, 2 parts of water, and 1.5 parts of polycarboxylic acid early strength type_CSP-12 water reducer.

[0192] Comparative Example 8

[0193] This comparative example uses a method for preparing inorganic artificial stone, using the formula of comparative example 7 for preparation, comprising the following steps:

[0194] After the above materials are weighed, white cement, 200 mesh calcium powder, metakaolin, and modified calcium carbonate powder are poured into the mixer in sequence and stirred at a speed of 300 rpm for 8 minutes; after sufficient stirring, water reducer, water, and polymer emulsion are added in sequence and stirred for a second time at a speed of 800 rpm for 12 minutes; after the second stirring is sufficient, fiber is added and stirred for a third time at a speed of 1200 rpm for 12 minutes, and the obtained mixture is poured into a mold and placed in a press for pressing. After the pressing is completed, the obtained rough material is cured at room temperature for 72 hours. After the curing is completed, the obtained square material is cut to 11 mm and polished to 10 mm to obtain the inorganic artificial stone.

[0195] The preparation steps of the modified calcium carbonate powder used therein are consistent with the preparation steps of the modified calcium carbonate powder in Example 8.

[0196] Comparative Example 9

[0197] This comparative example uses an inorganic artificial stone, the formula of which differs from that of Example 1 in that the calcium carbonate powder is not modified;

[0198] The specific formula of Comparative Example 9 is: 25 parts of Alborg white cement PW-1 52.5, 5 parts of 200 mesh calcium powder, 2 parts of metakaolin, 13 parts of 40 mesh calcium carbonate powder, 18 parts of 60 mesh calcium carbonate powder, 30.5 parts of 90 mesh calcium carbonate powder, 3 parts of styrene-butadiene emulsion, 0.3 parts of modified 6mm nylon fiber, 2 parts of water, and 1.5 parts of polycarboxylic acid early strength type_CSP-12 water reducer.

[0199] Comparative Example 10

[0200] This comparative example uses a method for preparing inorganic artificial stone, using the formula of comparative example 8 for preparation, comprising the following steps:

[0201] After the above materials are weighed, white cement, 200 mesh calcium powder, metakaolin, and calcium carbonate powder are poured into the mixer in sequence and stirred at a speed of 300 rpm for 8 minutes; after sufficient stirring, water reducer, water, and polymer emulsion are added in sequence and stirred for a second time at a speed of 800 rpm for 12 minutes; after the second stirring is sufficient, modified fiber is added and stirred for a third time at a speed of 1200 rpm for 12 minutes, and the obtained mixture is poured into a mold and placed in a press for pressing. After the pressing is completed, the obtained rough material is cured at room temperature for 72 hours. After the curing is completed, the obtained square material is cut to 11 mm and polished to 10 mm to obtain the inorganic artificial stone.

[0202] The modified fiber preparation steps used therein are consistent with the modified fiber preparation steps in Example 8.

[0203] Test Case

[0204] Test samples: The antibacterial ultra-thin inorganic artificial stones prepared in Examples 8-16 and the inorganic artificial stones prepared in Comparative Examples 2, 4, 6, 8, and 10 were used as samples.

[0205] Test method: The flexural strength and impact strength of the 10 mm ultra-thin plates in Comparative Examples 2, 4, 6, 8, and 10 and Examples 8-16 were tested respectively, and the 28d mechanical properties were compared. The detection method was based on GB / T35160-2017. The test results are shown in Table 1.

[0206] The antibacterial properties were tested according to JIS Z 2801:2010 (Tests for antibacterial activity and effectiveness of antibacterial products). Comparative Examples 2 and 6 did not have antibacterial effects and were only tested at 0 h and 24 h. The specific results are shown in Table 2 below.

[0207] Table 1

[0208] sample Flexural strength / MPa Impact strength / J Comparative Example 2 18.30 1.34 Comparative Example 4 21.32 1.68 Comparative Example 6 19.76 1.45 Comparative Example 8 22.37 1.71 Comparative Example 10 20.01 1.47 Example 8 22.93 1.83 Example 9 23.31 1.86 Example 10 23.47 1.88 Example 11 22.51 1.79 Example 12 22.87 1.84 Example 13 22.67 1.79 Example 14 22.71 1.80 Example 15 23.35 1.86 Example 16 23.29 1.84

[0209] Table 2

[0210]

[0211]

[0212] The data in Tables 1 and 2 indicate that the ultrathin artificial stone prepared in Example 10 exhibits the best overall performance in flexural strength, impact strength, and antibacterial properties at a thickness of 10 mm. This invention innovatively enhances the material's antibacterial and mechanical properties by combining calcium carbonate powder modified with a quaternary ammonium surfactant and silver ion-treated fibers.

[0213] in, Figure 1 This is a front view of the product of Example 10, Figure 2 This is a side view of the product of Example 10, Figure 3 It is a front view of Comparative Example 6; Figure 4-7 The following are the antibacterial test data analysis charts immediately after vaccination, 24 hours after vaccination, 168 hours after vaccination, and 720 hours after vaccination; Figure 8 This is a graph of flexural test data. In the graph, samples 1 to 14 correspond to comparative example 2, comparative example 4, comparative example 6, comparative example 8, comparative example 10, embodiment 8, embodiment 9, embodiment 10, embodiment 11, embodiment 12, embodiment 13, embodiment 14, embodiment 15, and embodiment 16, respectively. Figure 8 The bending strength is also called flexural strength; Figure 9 This is the experimental site picture of the flexural test. Figure 10 This is the front view of the falling ball impact test equipment. Figure 11 Side view of the falling ball impact test equipment.

[0214] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An antibacterial ultra-thin inorganic artificial stone, characterized in that: The invention comprises the following components: white cement, calcium powder, metakaolin, modified calcium carbonate powder, emulsion, modified fiber, water reducing agent and water; The modified calcium carbonate powder is obtained by modifying the calcium carbonate powder with a quaternary ammonium salt surfactant, and the modified fiber is obtained by modifying the fiber with silver ions.

2. The antibacterial ultra-thin inorganic artificial stone according to claim 1, characterized in that: The modified calcium carbonate powder includes at least one of 40-mesh modified calcium carbonate powder, 60-mesh modified calcium carbonate powder and 90-mesh modified calcium carbonate powder; And / or, the antibacterial ultra-thin inorganic artificial stone comprises the following components in parts by weight: 20-28 parts of white cement, 3-7 parts of calcium powder, 1-4 parts of metakaolin, 10-15 parts of 40-mesh modified calcium carbonate powder, 15-25 parts of 60-mesh modified calcium carbonate powder, 25-35 parts of 90-mesh modified calcium carbonate powder, 2-4 parts of emulsion, 0.3-1 part of modified fiber, 1-2.5 parts of water reducer and 2-4 parts of water.

3. The antibacterial ultra-thin inorganic artificial stone according to claim 1, characterized in that: Modifying calcium carbonate powder with a quaternary ammonium salt solution to obtain the modified calcium carbonate powder; And / or, the mass ratio of the quaternary ammonium salt solution to the calcium carbonate powder is 0.1 to 0.2; And / or, the concentration of the quaternary ammonium salt surfactant in the quaternary ammonium salt solution is 1%-5%; And / or, the quaternary ammonium salt surfactant includes at least one of cetyltrimethylammonium chloride and cetyltrimethylammonium bromide.

4. The antibacterial ultra-thin inorganic artificial stone according to claim 1, characterized in that: The raw material of the modified fiber includes at least one of 6mm nylon fiber and 6mm polyester fiber; and / or, modifying a modified fiber raw material by using a silver salt solution to obtain the modified fiber; and / or, the mass ratio of the fiber to the silver salt solution is 0.1 to 0.2; and / or, the AgCl concentration in the silver salt solution is 1% to 5%; And / or, during the treatment of the modified fiber, a glucose solution is further added, the mass ratio of the glucose solution to the silver salt solution is 0.5-1, and the concentration of the glucose solution is 10%-20%.

5. The antibacterial ultra-thin inorganic artificial stone according to claim 1, characterized in that: The white cement comprises at least one of Albow Cement PW-1 52.5 and Yingqi White Cement PW-1 52.5; And / or, the metakaolin has a SiO2 content of ≥50% and an Al2O3 content of ≥35%; And / or, the emulsion includes at least one of butadiene vinyl styrene copolymer emulsion, butadiene styrene emulsion, styrene acrylic emulsion, pure acrylic emulsion and acrylic acid emulsion.

6. The method for preparing the antibacterial ultra-thin inorganic artificial stone according to any one of claims 1 to 5, characterized in that: The following steps are involved: The antibacterial ultra-thin inorganic artificial stone is obtained by mixing white cement, calcium powder, metakaolin, modified calcium carbonate powder, emulsion, modified fiber, water reducer and water in a prescribed amount, and then performing molding and curing treatment in sequence.

7. The method for preparing the antibacterial ultra-thin inorganic artificial stone according to claim 6, characterized in that: The preparation process of the modified calcium carbonate powder includes: mixing calcium carbonate powder with a quaternary ammonium salt solution, stirring at a rotation speed of 600-1000 rpm for 20-30 minutes during the mixing process, then drying at a temperature of 25-50° C. for 8-24 hours, and then drying at a temperature of 60-80° C. for 3-12 hours to obtain the modified calcium carbonate powder.

8. The method for preparing the antibacterial ultra-thin inorganic artificial stone according to claim 6, characterized in that: The preparation process of the modified fiber includes: mixing the fiber with a silver salt solution, soaking the fiber at 25-60°C for 1-6 hours during the mixing process, then adding a glucose solution, reacting at 50-80°C for 3-12 hours, and heat-treating the fiber at 100-150°C for 0.25-1 hour after the reaction to obtain the modified fiber.

9. The method for preparing the antibacterial ultra-thin inorganic artificial stone according to claim 6, characterized in that: The mixing includes: White cement, calcium powder, metakaolin and modified calcium carbonate powder are stirred at a speed of 200 to 500 rpm for 5 to 12 minutes, and then a water reducer, water and emulsion are added and stirred at a speed of 600 to 1000 rpm for a second time for 10 to 15 minutes, and then modified fiber is added and stirred at a speed of 1000 to 1300 rpm for a third time for 10 to 15 minutes to obtain a mixture, and the mixture is pressed and cured in sequence; And / or, the curing time is 48 to 96 hours.

10. Use of the antibacterial ultra-thin inorganic artificial stone according to any one of claims 1 to 5 or the method for preparing the antibacterial ultra-thin inorganic artificial stone according to any one of claims 6 to 9 in preparing artificial stone.

Citation Information

Patent Citations

  • A method for preparing antibacterial artificial stone and an operating room wall panel using this stone.

    CN110590239B

  • A long-lasting antibacterial artificial stone and its preparation process

    CN110590241B

  • Antibacterial artificial stone and its preparation method, building materials

    CN111302704B